Case Report: A simple case of drug-induced secondary antibody deficiency or a rare primary immune deficiency? - Johnston, Sarah L.; Evans, Julie C.; Berry, Ian R.; Watkinson, Oliver T. (Frontiers in Immunology, 2025)
Antibody deficiency may be primary, because of an underlying inborn error of immunity, or secondary, due to another disease process or medication, leading to decreased antibody production or increased antibody loss. Secondary antibody deficiency is much more common than primary. It can, however, be difficult to distinguish primary from secondary, and both should be considered when assessing patients with hypogammaglobulinaemia. The case presented highlights the importance of confirming the underlying pathophysiology in patients presenting with antibody deficiency, the contribution of genetic assessment to the care of patients with complex phenotypes, and the impact this can have on long-term patient management.